The Potency of Polymeric Nanoparticles as New Drug Delivery System: A Narrative Review - Ariesaka, Kiky M.; Hidayati, Zulfa; Nurhayati, Siti; Dewi, Ni L.M.N.; Nuryady, Moh M. (Universitas Padjadjaran, Indonesia, 2025)
Polymeric nanoparticles are particles ranging from 1 to 1,000 nm that can be loaded with active compounds. Polymeric nanoparticles can be classified based on their morphological structure into nanocapsules and nanospheres. In addition, polymeric nanoparticles can also be classified based on the compound’s origin into natural and synthetic polymer. The nanoparticle production method is adjusted based on the type of drug that will be loaded. The methods commonly used for the production of polymeric nanoparticles are solvent evaporation, solvent emulsification/ diffusion, nanoprecipitation, emulsification/ reverse-salting out, and nanoprecipitation. This review also provides several examples of clinical applications of nanoparticles in the formulation of several drugs/bioactives including hyperforin, curcumin, and amphotericin B.